Rancang Bangun Game 2D " East Java Adventure" Menggunakan Unity - Filsa Okta Ari Putri; Cindy Taurusta (Journal of Animation and Games Studies, 2023)
Young generations in Indonesia experience stress during the Covid-19 pandemic. To help reduce stress, this study aims to design a 2D game called "East Java Adventure" for the young generation aged 12 years and over via a personal computer with a Windows system. To design and develop this game, the researcher utilized various hardware and software such as Unity 2D, blender, and Photoshop. This game was tested for validity using a black box. The testing involved 10 children aged 15 years and older. The results of this study showed that 95% of "East Java Adventure" game users were interested in this game. They considered this game very satisfying due to its success in testing patience, complete features, and easy-to-understand UI display. Thus, this game is worthy of being published and is expected to help overcome stress in the younger generation in Indonesia.